2011
DOI: 10.1590/s0004-28032011000400002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, endoscopic and histopathological profiles of parasitic duodenitis cases diagnosed by upper digestive endoscopy

Abstract: -Context -Intestinal parasites induce detectable histopathological changes, which have been studied in groups with known diagnosis of parasitic disease. There is no available study with a larger base without previous diagnosis. Objective -To describe clinical and histopathological findings of parasitosis diagnosed by endoscopic biopsy in patients submitted to upper digestive endoscopy.Methods -Recorded biopsies archive at "Complexo Hospitalar Professor Edgar Santos", a general teaching Hospital in the state of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 12 publications
3
17
0
Order By: Relevance
“…In S stercoralis infection, presence of protein-losing enteropathy was also observed. The most common histopathological findings showed oedema and infiltration of the lamina propria by lymphocites and plasmocites, shortened or absent villus, cryptitis and crypt hyperplasia, epithelial layer infiltration by numerous intraepithelial lymphocites and antigen-presenting cells and the presence of lymphagectasia,23 as reported in this case.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In S stercoralis infection, presence of protein-losing enteropathy was also observed. The most common histopathological findings showed oedema and infiltration of the lamina propria by lymphocites and plasmocites, shortened or absent villus, cryptitis and crypt hyperplasia, epithelial layer infiltration by numerous intraepithelial lymphocites and antigen-presenting cells and the presence of lymphagectasia,23 as reported in this case.…”
Section: Discussionsupporting
confidence: 73%
“…Loutfy and others had reported 94.6% enzyme immunoassay sensitivity, Van Doorn reported for enzyme immunoassay a specificity ranging from 95% to 97.7% and a sensitivity of 83–93% depending on the test used 10 12. Santos et al 23 reported that eosinophilia was not a common finding in their study, only one of eight patients with S stercoralis infection had eosinophilia.…”
Section: Discussionmentioning
confidence: 82%
“…Invasive methods like endoscopy with duodenal aspirate or biopsy can also be used in patients with strong clinical suspicion of infection. Upper endoscopic exam may show normal looking mucosa with eosinophilic infiltration on pathological examination or it may show abnormal mucosa in the form of erosions and ulcerations with pathological examination characterized by cryptitis, crypt abscess and eosinophilic infiltration [36,37] . Similarly the colon, particularly rightsided colon, may get involved in the presence of overwhelming parasite burden.…”
Section: Diagnostic Methodsmentioning
confidence: 99%
“…The clinical manifestations (abdominal pain and watery diarrhea), along with the histological picture, often resemble celiac disease. In these cases eosinophilia may occur and a careful examination may identify the parasite in biopsy and fecal samples [80-82]. Elevated IELs count are also found in viral enteritis [83].…”
Section: Origin Of Mementioning
confidence: 99%